G342(P) Reducing anxiety in staff caring for patients with tracheostomies through a multi-modal simulation study day. (24th May 2017) - Williams, NM; Davison, C; Hossain, A; Nicholl, M
Abstract : Background: Despite being one of the oldest medical procedures known, tracheostomies still causes medical professionals a great deal of anxiety 1, 2 . Lack of confidence in caring for these patients relate to infrequent exposure of patients with tracheostomies, lack of formalised teaching and uncertainty regarding local policies 3 . We developed an inter-disciplinary tracheostomy study day and assessed whether participation in the course reduced anxiety levels. Methodology: Participants completed a pre and post course questionnaire including a modified Spielberger State-Trait Anxiety Inventory which is a validated tool to measure anxiety 4, 5 . Data was collected anonymously and analysed using Excel. Means were compared using student t-test using a p-value significance of <0.05. Free text comments were analysed into themes using a pragmatic approach to framework analysis. Results: 16 participants attended the study day and completed the pre and post course questionnaire. Pre-course anxiety scores were an average of 9.6 out of a possible maximum of 24. Post-course anxiety scores were an average of 8.2 out of a possible 24. This was statistically insignificant with a p-value of 0.16. 94% of participants felt moderately or very confident in caring for patients with tracheostomies after completing the course. Free text comment analysis showed that much of the anxiety around caring for patients with tracheostomies relates to lack of previous experience and the 'high stakes' involved in any complications that may arise. Participants' views on the structure and content of the course itself will be presented in a separate abstract. Discussion: Our findings suggest that a one day tracheostomy study day including interactive lectures and small group simulation workshops can lead to a reduction in anxiety around caring for patients with a tracheostomy. Though the results are not statistically significant this is likely to be due to small numbers with lack of statistical power. Our study supports previous literature that suggests that staff are anxious about caring for patients with tracheostomies due to lack of exposure and experience but that this anxiety can be lessened through educational programmes.